On the stability of coherent HfRu- and ZrRu-B2 precipitates in Nb-based alloys - Carolina Frey; Benjamin Neuman; Kaitlyn Mullin; Anthony Botros; James Lamb; Collin S. Holgate; Sebastian A. Kube; Tresa M. Pollock (Materials & Design, 2024)
High temperature creep strengths of Nb-based alloys have been limited by the lack of coherent precipitates that exist at temperatures above 1200Image 1. In this investigation, a series of BCC Nb-based alloys with coherent HfRu- and ZrRu-B2 precipitates were investigated to determine the dependence of phase stability, misfit, and solvus temperatures on composition. Sequential anneals from 1000-1500Image 1 were used to determine the B2 solvus temperature (Ts,B2) of each alloy and solvus lines were constructed for each system. HfRu-B2 is found to be more thermally stable than ZrRu, with HfRu-containing alloys demonstrating higher Ts,B2 at equivalent Ru concentrations. For alloys with Ts,B2 above 1200Image 1, additional anneals at 1000 and 1200Image 1 provide insight into B2 volume fraction variations with temperature. Additional Hf- and Zr-rich tertiary phases also formed on the grain boundaries of the selected compositions at intermediate to high temperatures. Through transmission electron microscopy, the lattice misfits for the B2 precipitates were found to be ≈ 0.5% at 1000Image 1 and the grain boundary phases were identified as C14 Laves, L10, β-Hf, and topologically close-packed P phases. Implications for the design of Nb-based alloys strengthened by Ru-B2 precipitates, including strategies to mitigate deleterious phase formation, are discussed throughout.